STEERABLE TOROIDAL BIFOCAL LENS-ARRAY ANTENNA IN 57–64 GHZ RANGE - Alexander A. Maltsev; Valentin M. Seleznev; Alexander S. Rulkov; Olesya V. Bolkhovskaya (Известия высших учебных заведений России: Радиоэлектроника)
Introduction. Currently, one of the most promising approaches to the development of 5th generation mobile wireless systems is the deployment of heterogeneous networks based on existing LTE cellular systems having both large and small cells. Small, low-cost relay stations equipped with highly directional steerable antenna systems to connect small cells with LTE base station serving macrocell can comprise the main elements of such networks. Objective. Since existing solutions are either too expensive or do not allow the flexible rearrangement of current information transmission lines, the objective of this work is to develop antenna equipment for low-cost relay stations based on simple, steerable antenna systems of millimetre wavelength (57-64 GHz), which allow beamsteering on both azimuth and elevation planes. Methods and materials. The developed steerable, bifocal lens antenna system comprises a specially-shaped lens made of high-molecular-weight polyethylene and integrated with a phased array antenna. A key feature of its design is a wide-angle beamsteering in the azimuth plane and ability to adjust the beam in the elevation plane. The calculation of the lens profiles was carried out by means of an approximation of geometrical optics in Matlab, while the main technical characteristics of the lens antenna system were obtained by direct electromagnetic modelling in CST Microwave Studio. Results. A prototype steerable, bifocal lens-array antenna system has been developed and its characteristics studied. The following technical characteristics are achieved in the 57–64 GHz range: beamsteering in the elevation plane – ±3º; beam-steering in the azimuth plane – ±40º; antenna gain – from 20 to 27.5 dBi for all angles. Conclusion. It is shown that the developed antenna system can be successfully used as a component of the receiving and transmission equipment of small relay stations that transmit information in the frequency range of 57-64 GHz over a distance of 100-300 m.